A profile of cutaneous tuberculosis - Patra Apares; Gharami Ramesh; Banerjee Paritosh (Wolters Kluwer Medknow Publications, 2006)
About 39330, new patients were examined over a period of two years and it was revealed that 104 patients (0.26%) had cutaneous tuberculosis. Most of the tuberculosis patients (61.52%) were between the age of 5 to 25 years. Lupus vulgaris was the commonest variant (57.69%), followed by scrofuloderma (21.15%). Males suffered more than females (2.25:1) and all patients belonged to lower socio-economic class. 62 cases (59.61%) showed evidence of BCG vaccination that failed to protect cutaneous tuberculosis. Mantoux test was positive in all cases except 4. Bacteriological examination was negative in all cases. Response to antitubercular therapy was very good except in two cases which required addition of an extra drug and also took more time.